21st Century Skills: A Proposal for ELT Teachers Successful Performance Today - López Prieto, Adriana (Coloquio, 2023)
This article addresses a reflective study on 21st century ELT teachers’ necessary skills at school level in Colombia. The study aimed to analyze a set of abilities that enable teachers to perform successfully in a contemporary classroom setting by understanding the pivotal role of ICTs, adaptability, and communicative-social skills to guarantee the accomplishment of students’ expected learning outcomes. Data were collected through documentary analysis of academic research articles. Findings revealed that mastering 21st century teaching skills equips ELT educators with the required knowledge to provide students with a rewarding learning experience. As a conclusion, the integrative employment of a particular array of skills aligned with present-day educational standards cultivates highly proficient teachers who are capable of effectively navigating both their teaching context and that of their students.